University Students’ Perceptions of the Effects of Teacher Self-Disclosure in the English Language Classroom - Mohsine Jebbour (Yayasan Visi Intan Permata, 2018)
The purpose of this study was to elicit university students’ views about the potential effects that teacher self-disclosure may have in the English language classroom. Teacher self-disclosure—defined as the use of personal information to explain the course content to students in the classroom—was implemented in the ‘spoken English’ course in three sessions. The research method for data collection was interviewing 15 first year students attending the course. Thematic analysis was employed to develop common themes from the respondents’ answers. Results suggest that teacher self-disclosure might be used as an effective instructional practice to increase student motivation, develop a positive teacher-student relationship, enhance cognitive learning, and seek students’ attention in the learning process.